Assessment of Ionizing Radiation Dose and Risk Levels associated with Radioactivity in Oraifite, Nigeria. - Anekwe, Uzo (European Journal of Applied Sciences, 2020)
Radioactivity has been natural occurrence in human environment and its adverse effects are highly undesirable. This study assessed radiation risk levels associated with radioactivity in Oraifite using gamma ray (Ɣ-ray) spectrometry and radiation survey meter. The mean value of background ionizing radiation (BIR) exposure rate ranged from 0.011 to 0.014mRh-1. The mean activities of 226Ra, 232Th, 40K ranged from 23.54±4.89 to 41.03±4.28 BqKg-1, 9.69±1.88 to 11.34±1.86 BqKg-1, 419.22±3.41 to 737.91±4.78 BqKg-1 respectively. Mean values of radium equivalent (Raeq), absorbed dose (D), Igamma (IƔ), internal hazard index (Hin), external hazard index (Hex) and annual effective dose equivalent (AEDE), were 60.05Bqkg-1, 55.75nGh-1, 0.86, 0.41, 0.30 and 0.07mSvy-1 respectively. Excess lifetime cancer risk (ELCR) which is estimation of the probability of cancer incidence in a population of individuals for a specific lifetime had a mean value of 0.25x10-3 and this is lower than the world permissible limit of 0.29x10-3. The average dose to human organs/tissues; lungs, ovaries, bone marrow, testes, kidney, liver and whole body were 0.033, 0.028, 0.033, 0.040, 0.028, 0.023, and 0.033 mSvy-1 respectively, meaning that all the computed organ dose were far much lower than the maximum allowable standard value of 1.0 mSvy-1. Virtually all hazard indices were below the ICRP recommended values and in general the residents of Oraifite are not under ionizing radiation threat.